A Study to Determine The Factors Affecting on The Compulsive Purchase - Günaydın, Özge Elmas (Fırat University, 2021)
Technological developments cause differentiation in consumption habits. The coexistence of physical and online channels increases the availability of products and creates a craze for consumption. As a result of the relevant situation, individuals may become unable to control themselves while meeting their wishes and needs. The buying behavior performed by the consumers because of the impulses that cannot be prevented is called compulsive, in other words, obsessive buying. Compulsive buying behavior drives individuals to social and financial difficulties. In this study, it was aimed to determine the variables that affect compulsive buying behavior by using field research method. According to the results of the study; postmodern consumption behaviors, psychological conditions, personal factors, technology, promotion efforts and brand behaviors, and demographic and social factors have an effect on compulsive purchasing buying.

Teknolojik gelişimler tüketim alışkanlıklarında farklılaşmalar meydana getirmektedir. Fiziksel ve online kanalların birlikteliği ürünlere her zaman ulaşılabilmesi durumu artırarak tüketim çılgınlığını ortaya çıkarmaktadır. İlgili durum sonucunda bireyler istek ve ihtiyaçlarını giderirken kendini kontrol edemez duruma gelebilmektedir. Tüketicilerin engelleyemediği dürtüleri sebebiyle gerçekleştirdiği satın alma davranışına kompulsif diğer bir ifade ile takıntılı satın alma denir. Kompulsif satın alma davranışı bireyleri sosyal ve maddi zorluklara sürüklemektedir. Bu çalışmada kompulsif satın alma davranışı üzerinde etkili olan değişkenlerin alan araştırması yöntemi ile belirlenmesi amaçlanmıştır. Çalışma sonuçlarına göre; postmodern tüketim davranışları, psikolojik durumlar, kişisel faktörler, teknoloji, tutundurma çabaları ve marka davranışları ile demografik ve sosyal unsurlar kompulsif satın alma davranışı üzerinde etkili olmaktadır.
KOMPULSİF SATIN ALMA ÜZERİNDE ETKİLİ OLAN FAKTÖRLERİN BELİRLENMESİNE YÖNELİK BİR ARAŞTIRMA